2016
DOI: 10.1111/anae.13388
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hydroxyethyl starch 6% 130/0.4 compared with gelatin on microvascular reactivity

Abstract: SummaryWe compared the effects on microvascular reactivity of hydroxyethylstarch (Volulyte â ) and gelatin (Geloplasma â ) during acute haemodilution. The hypothesis was that Volulyte would provide better microvascular reactivity than Geloplasma. Forty patients undergoing elective cardiac surgery were randomly assigned to receive either Volulyte or Geloplasma as the exclusive priming solution of the cardiopulmonary bypass. To evaluate microvascular reactivity, postocclusive reactive hyperaemia was examined bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
(40 reference statements)
0
7
0
1
Order By: Relevance
“…Perfusate oncotic pressure is usually adjusted by addition of high molecular weight components such as HES or gelatine that should secure a stable preparation and minimise cytokine production and oedema formation. The setting of IPL is similar to the situation after extracorporeal circulation in cardiac surgery with dilution of the blood volume with up to 1.5 liters of gelatine or HES containing fluids 2 , 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Perfusate oncotic pressure is usually adjusted by addition of high molecular weight components such as HES or gelatine that should secure a stable preparation and minimise cytokine production and oedema formation. The setting of IPL is similar to the situation after extracorporeal circulation in cardiac surgery with dilution of the blood volume with up to 1.5 liters of gelatine or HES containing fluids 2 , 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, monitoring microvascular reactivity could be a useful method for guiding fluid therapy . In a study by Moerman et al , the authors evaluated HES and gelatin as priming solutions for the cardiopulmonary bypass circuit. They concluded that HES 130/0.4 maintains better microvascular reactivity than gelatin during acute haemodilution.…”
Section: Discussionmentioning
confidence: 99%
“…The best fluid resuscitation strategy after cardiac surgery and, generally speaking, in critical patients, is still a topic of great debate, with contrasting results. 14,15 Perhaps the key point is not which fluid to administer, but timing of administration, selection of patients, and global dose of fluids together with the monitoring systems used to guide fluid resuscitation. Indications, monitoring, and timing of fluid administration should be addressed precisely in a well-powered, focused trial.…”
Section: Referencesmentioning
confidence: 99%